The interaction between Myc and Miz1 is required to antagonize TGFβ-dependent autocrine signaling during lymphoma formation and maintenance - van Riggelen, Jan (Cold Spring Harbor Laboratory Press, 2010)
The Myc protein suppresses the transcription of several cyclin-dependent kinase inhibitors (CKIs) via binding to Miz1; whether this interaction is important for Myc's ability to induce or maintain tumorigenesis is not known. Here we show that the oncogenic potential of a point mutant of Myc (MycV394D) that is selectively deficient in binding to Miz1 is greatly attenuated. Binding of Myc to Miz1 is continuously required to repress CKI expression and inhibit accumulation of trimethylated histone H3 at Lys 9 (H3K9triMe), a hallmark of cellular senescence, in T-cell lymphomas. Lymphomas that arise express high amounts of transforming growth factor β-2 (TGFβ-2) and TGFβ-3. Upon Myc suppression, TGFβ signaling is required to induce CKI expression and cellular senescence and suppress tumor recurrence. Binding of Myc to Miz1 is required to antagonize growth suppression and induction of senescence by TGFβ. We demonstrate that, since lymphomas express high levels of TGFβ, they are poised to elicit an autocrine program of senescence upon Myc inactivation, demonstrating that TGFβ is a key factor that establishes oncogene addiction of T-cell lymphomas.